Cover Image. (10th October 2021) - Zhu, Sha; Ni, Yuchao; Sun, Guangxi; Wang, Zilin; Chen, Junru; Zhang, Xingming; Zhao, Jinge; Zhu, Xudong; Dai, Jindong; Liu, Zhenhua; Liang, Jiayu; Zhang, Haoran; et al.
Abstract : The cover image is based on the Research Article Exosomal TUBB3 mRNA expression of metastatic castration‐resistant prostate cancer patients: Association with patient outcome under abiraterone by Hao Zeng et al., https://doi.org/10.1002/cam4.4168 .